2011
DOI: 10.1002/pbc.23343
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of NTRK family gene expression in neuroblastomas

Abstract: Background Neuroblastomas (NBs) are characterized by clinical heterogeneity, from spontaneous regression to relentless progression. The pattern of NTRK family gene expression contributes to these disparate behaviors. TrkA/NTRK1 is expressed in favorable NBs that regress or differentiate, whereas TrkB/NTRK2 and its ligand BDNF are co-expressed in unfavorable NBs, representing an autocrine survival pathway. We determined the significance of NTRK family gene expression in a large, representative set of primary NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…We also evaluated MYC and MYCN expression, which are downregulated in RA-sensitive cells by 13- cis RA(33, 34), and NTRK1 and NTRK2, which are upregulated in response to 13- cis RA(35). Expression of these proteins in primary tumors correlates with clinical outcomes(36, 37). We confirmed the increase of PBX1 expression, observed as isoforms PBX1a and PBX1b, in RA-sensitive cell lines treated with 13- cis RA, and associated with changes in MYCN, MYC, NTRK1, and/or NTRK2 (Figure 2A–C).…”
Section: Resultsmentioning
confidence: 99%
“…We also evaluated MYC and MYCN expression, which are downregulated in RA-sensitive cells by 13- cis RA(33, 34), and NTRK1 and NTRK2, which are upregulated in response to 13- cis RA(35). Expression of these proteins in primary tumors correlates with clinical outcomes(36, 37). We confirmed the increase of PBX1 expression, observed as isoforms PBX1a and PBX1b, in RA-sensitive cell lines treated with 13- cis RA, and associated with changes in MYCN, MYC, NTRK1, and/or NTRK2 (Figure 2A–C).…”
Section: Resultsmentioning
confidence: 99%
“…Like TrkB, TrkA and TrkC are up-regulated in many types of cancers and demonstrated to be oncogenic as well (13). For example, Light et al (87) reported TrkA up-regulation in neuroblastomas was associated with poor prognosis, while activated expression and signaling of TrkC corresponded to a more aggressive and invasive neuroblastoma. Besides, the kinase domain of the three receptors are remarkably conservative.…”
Section: Clinical Trials Of Targeting Trk Receptors For Treatment Of mentioning
confidence: 99%
“…In addition, TRKC and very recently TRKB have also been shown to form oncogenic chimeras in multiple tumor types [12,13]. Aside from gene fusions, only an in-frame deletion of NTRK1 in acute myeloid leukemia and a splice variant of NTRK1 in neuroblastoma have been functionally characterized as oncogenic to date [14][15][16][17][18]. However, no reports are available on the effects of NTRK gene amplification (defined as ≥ 4.0 copies).…”
Section: Introductionmentioning
confidence: 99%